Cloud based sensor network for environmental monitoring. (March 2018) - Corbellini, S.; Di Francia, E.; Grassini, S.; Iannucci, L.; Lombardo, L.; Parvis, M.
Abstract: This paper describes a complete infrastructure for environmental monitoring, which is based on a cloud architecture. The proposed system employs small button-like battery-operated sensors, which connect through a wireless link to small receivers capable of routing data to the cloud system. Cloud data can be accessed in real time through smart-phones and downloaded for further analyses. Each button-like sensor is capable of measuring temperature and humidity for more than one year without attendance. All data are sent to the receiver and in addition stored inside the button memory so that the system can work also in the absence of power and Internet connection. The architecture takes advantage of the μ Panel environment, which is conceived to work also with unreliable and slow Internet connections and permits to implement a cloud-based infrastructure with the capability to control the sensors locally and in absence of Internet connectivity. The proposed architecture is currently used in different museums to monitor the local environment inside the display rooms, but the system can be easily extended to open environments without additional costs.